Penguatan Modal Sosial Sebagai Upaya Pengembangan Ekonomi dan Kapasitas Rumah Tangga Nelayan Berkelanjutan di Desa Pangandaran - Dandy E Prasetiyo; Firman Zulfikar; Siti Aisyah Ningrum (Journal Omni-Akuatika, 2016)
This research was conducted Pangandaran District, Pangandaran Regency. The purpose of this study was to analyze the existing social conditions and to performe system analyze of social capital to be used as a strategy to improve the economy and the capacity of households of fishermen. The data was collected through the secondary data obtained from goverment offices and primary data was generated from interviews with fishermen household, village governments, and institutions or social organizations associated with fishing. The research instrument used is Social Capital Assessment Tool (SOCAT). Data were analyzed using descriptive qualitative method. Social capital research was assessed based on the profession similarity. The results showed that social capital was presumably beneficial for fishermen households by boosting the economy level and welfare as well as their capacity building. Institutions or social organizations in the village of Pangandaran namely Business Group (KUB), the Regional Commissioner (Komda), Rukun Fisherman (RN), the Fishermen Association of Indonesia (HNSI), and the Village Unit Cooperatives (KUD). Institutions or institutional activity may stimulate the further development and productivity of the coastal community. As most of the coastal communities depend on the limited marine resources, social capital strengthening can be a promising approach for expansion and development of existing networks. The strategy can be applied was the involvement of other family members to participate on any form of institutional bodies dedicated for coastal community.Keywords : social capital, coastal, fishermen households